2004
DOI: 10.1016/j.jlumin.2003.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational echo correlation spectroscopy probes of hydrogen bond dynamics in water and methanol

Abstract: Multidimensional vibrational echo correlation spectroscopy with full phase resolution is used to measure hydrogen bond dynamics in water and methanol. The OD hydroxyl stretches of methanol-OD oligomers in CCl(4) and HOD in H(2)O are studied using the shortest mid-IR pulses (<50 fs, <4 cycles of light) produced to date. The pulses have sufficient spectral bandwidth to span the very broad (>400 cm(-1)) spectrum of the 0-1 and 1-2 transitions. Hydrogen bond population dynamics are extricated with exceptional deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
113
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(114 citation statements)
references
References 56 publications
0
113
0
1
Order By: Relevance
“…The frequency changes are reflected in the change in shapes of the 2D-IR vibrational echo spectra. Full descriptions of the method have been presented (16,(38)(39)(40). (41) and are shifted along the m -axis by the CO stretching mode's anharmonicity.…”
Section: Resultsmentioning
confidence: 99%
“…The frequency changes are reflected in the change in shapes of the 2D-IR vibrational echo spectra. Full descriptions of the method have been presented (16,(38)(39)(40). (41) and are shifted along the m -axis by the CO stretching mode's anharmonicity.…”
Section: Resultsmentioning
confidence: 99%
“…49 Here, we present a detailed account of the vibrational echo experiments on AOT reverse micelles that have been reported previously, 49 including new frequency-dependent data, as well as vibrational pump-probe experiments that examine the population dynamics of the hydroxyl stretch. Vibrational echo spectroscopy [16][17][18]20,[50][51][52][53][54][55][56] is uniquely capable of determining system dynamics by removing the inhomogeneous broadening contribution from the line shape 16,[56][57][58][59][60][61][62] and tracking the underlying dynamics. 63, 64 The properties of hydrogen-bond networks can be studied using IR spectroscopy of the hydroxyl stretching mode, because of the strong influence of the number and strength of hydrogen bonds on the hydroxyl stretch frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Recent experiments had demonstrated that two-dimensional infrared (2D IR) lineshapes can probe the picosecond dynamics of chemical exchange by observing coherence transfer in molecular vibrations through time-dependent spectral jumps 1,2,3 . This spectroscopic technique 4,5,6 is an optical analogue of 2D NMR commonly used to study slower (ms) chemical exchange processes 7,8,9,10 .…”
Section: Introductionmentioning
confidence: 99%